Expression of lymphangiogenesis marker Prox-1 in ovarian cancer - Mazurek, Magdalena; Bednarek, Wiesława; Jach, Robert; Kotarski, Józef (Menopause Review/Przegląd Menopauzalny, 2009)
Lymphangiogenesis in ovarian cancer is not yet well characterised. Lymphatic vessels help tumor progression, and simultaneously represent the most important pathway for neoplastic cell dissemination. The estimation of the lymphatic endothelium markers expression can be useful in the evaluation of lymphangiogenesis, cancer progression and ability of metastatic spreading. It is especially interesting the research on specific lymphatic markers, such as Prox-1, nuclear transcription factor. We investigated correlation between expression of Prox-1, histological type and grading of ovarian cancer. Our studies show the expression of Prox-1 in all investigated histological types of ovarian cancer. We did not observe the statistis correlation (p > 0.05) with reference to type and grading. Further investigations taking into account bigger number of patients, spectrum of operation, and other exponents of limphangiogenesis, probably allow to discover different correlations.